Genome-wide chromatin interactions of the Nanog locus in pluripotency, differentiation and reprogramming - Apostolou, Effie (2013)
While the chromatin state of pluripotency genes has been extensively studied in embryonic stem cells (ESCs) and differentiated cells, their potential interactions with other parts of the genome remain largely unexplored. Here, we identified a genome-wide, pluripotency-specific interaction network around the Nanog promoter by adapting circular chromosome conformation capture-sequencing (4C-seq). This network was rearranged during differentiation and restored in induced pluripotent stem cells. A large fraction of Nanog-interacting loci were bound by Mediator or cohesin in pluripotent cells. Depletion of these proteins from ESCs resulted in a disruption of contacts and the acquisition of a differentiation-specific interaction pattern prior to obvious transcriptional and phenotypic changes. Similarly, the establishment of Nanog interactions during reprogramming often preceded transcriptional upregulation of associated genes, suggesting a causative link. Our results document a complex, pluripotencyspecific chromatin "interactome" for Nanog and suggest a functional role for longrange genomic interactions in the maintenance and induction of pluripotency.